Analysis of the Raw Material Inventory Control to Improve Cost Efficiency PT Pupuk Indonesia - Aisyah - Salsabila; Hadiahti - Utami; Achmad - Zaenuddin (Politeknik Negeri Semarang, 2022)
World commodity prices rose due to the pandemic, the energy crisis in Europe and several countries that have policies to stop their exports, the increase in the price of KCL and DAP raw materials due to export restrictions carried out by Russia and China. The data analysis techniques used are collecting data containing information on raw material inventory in 2021, processing inventory control data based on company policies, calculating inventory costs using a just in time system, data analysis and drawing conclusions KCL needs 53,627 frequency of purchases 4 times the total inventory costs of Rp. 460,827,437. 20 times the total cost of supply Rp. 202,764,072. 1 time the total cost of supply Rp. 921,654,874. 11 times the total cost of inventory is Rp. 276,496,462. The needs of 69,138 DAP purchase frequency 6 times the total cost of inventory Rp. 829,043,491. 24 times the total cost of inventory Rp. 404,573,224. 5 times the total cost of supply Rp. 890,061,092 and 11 times the total cost of supply Rp. 606,859,835. The biggest saving value on KCL raw materials is to make a frequency of purchases as much as 20 times, inventory costs borne by the company Rp. 202,764,072 so as to save costs of Rp. 718,890,802. Meanwhile, DAP raw materials can make purchases as much as 24 times with inventory costs borne by the company of Rp. 404,573,224, so that the company can save costs of Rp. 1,618,292,894.